Os processos de des-re-territorialização na implantação do complexo energético Amador Aguiar (MG) e os atingidos não-proprietários de terras - Silva, Rene Gonçalves Serafim (2014)
This work is the result of a research about Great Hydroelectric Projects (GHP) and the process of de-re-territorialisation of affected people in the river basin Araguari, Minas Gerais. The Amador Aguiar Energy Complex, an enterprise composed by Consórcio Capim Branco Energia (CCBE), was chosen as a case report. This study aimed to describe and analyze the implementation and operation of this project and understand the process of de-re-territorialisation triggered as social and spacial effects in an enterprise of this size. The study subjects, the affected non-landowners, were chosen as a research resource for understanding this de-re-territorialisation. As a methodological procedure, were raised and discussed relevant references about the theme and geographical analysis categories, such as place and territory. The implementation and operation of hydropower plants Amador Aguiar I and II, composed by Amador Aguiar Power Complex, were described and analyzed, besides the composition of Consórcio Capim Branco Energia (CCBE). Finally, the implementation of two rural settlements was discussed (Olhos D\'Água and Vida Nova), both in Uberlândia (MG), to attend the non- affected landowners who chose to remain on the land. These settlements were the option given by the consortium as a form of compensation, being awarded with small land where they could reterritorialize and conduct their economic activities. The conclusion is that the affected who resides in each settlements has different realities today. Most owners of lands in the settlement Olhos D\'Água, for those who are still there, use them only as property and cannot reproduce economically, as predicted by the consortium. Some owners sold their lands and migrated due to the economic situation in which they found themselves. In contrast, the residents of the settlement Vida Nova managed to restore these new territories due to a number of factors that favored them, such as the location next to the displacement place, proximity to the water dam Amador Aguiar I hydropower plant and their developed economic activities. However, they still do not have the contract of their properties and there is a fear that they may get a new displacement.